Medical causes and histological pattern of glomerulonephritis - Abdullah, AB; Khanam, A; Biswas, SK; Nilov, A; Shahin, A MA; Murshed, KM; Sultana, T (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jan;17(1):38-41. The abstract of this article is available on the PubMed website